2005
DOI: 10.1121/1.2011127
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation by vortex induced flexible wall vibration

Abstract: Sound radiation due to unsteady interaction between an inviscid vortex ͑which models a turbulent eddy͒ and a finite length flexible boundary in a two-dimensional space is studied using potential theory and the matched asymptotic expansion technique. The Mach number of the vortex propagation is kept below 0.15. Results suggest that the monopole field created by the volumetric flow induced by the vibrating flexible boundary dominates the overall acoustic power radiation. The longitudinal dipole directly due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 32 publications
6
11
0
Order By: Relevance
“…The flexible walls are modeled as membranes with tension per unit length T, mass density m, and a damping coefficient D as in Huang 10 and in the previous investigations of the authors. 13,19 In the foregoing sections, a and (x o , y o ) represent the width of the duct and the instantaneous vortex position, respectively. The length and height of the cavity are denoted by L and h, respectively.…”
Section: Theoretical Developementmentioning
confidence: 99%
See 3 more Smart Citations
“…The flexible walls are modeled as membranes with tension per unit length T, mass density m, and a damping coefficient D as in Huang 10 and in the previous investigations of the authors. 13,19 In the foregoing sections, a and (x o , y o ) represent the width of the duct and the instantaneous vortex position, respectively. The length and height of the cavity are denoted by L and h, respectively.…”
Section: Theoretical Developementmentioning
confidence: 99%
“…For small membrane vibration magnitudes, the vibrating membranes are modeled as rigid boundaries with distributed fluctuating normal velocities as in Tang et al 13 The complex flow potential at any position (x, y) inside a channel, W, due to a flow of velocity v into the channel through a tiny opening of width Dx at…”
Section: A Vortex Velocity and Membrane Vibrationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the flow structure-acoustics interaction therefore is important for improved duct noise control design. Tang et al [13] developed a theoretical model to investigate the sound generated by the unsteady interactions between a vortex and a finite length flexible boundary in an otherwise rigid wall at low Mach numbers. It is concluded that the time fluctuating volumetric flow rate induced by the flexible boundary vibration and the vortex acceleration are two major sources of sound.…”
Section: Introductionmentioning
confidence: 99%